Analisis Kesulitan Belajar Matematika Materi Bangun Datar Kelas IV SD 1 Gondosari - Silvi Mutia; Aminatus Sholihah; Bintang Cahyani; Widya Anggun Damayanti; Fina Fakhriyah; Nur Fajrie (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to analyze the learning difficulties of fourth grade students on flat building material at SD 1 Gondosari, Gebog, Kudus Regency. The method used is qualitative with a case study approach. Data were obtained through questionnaires and interviews involving students and teachers as research subjects. The results showed that students' learning difficulties were influenced by internal and external factors. Internal factors include negative attitudes towards mathematics, lack of understanding of concepts, difficulties in numeracy skills, and problem-solving ability. External factors include less than optimal use of learning media and lack of attention from parents. The findings show that students' main difficulties are in understanding the concept of the formula, calculating the square area, and solving varied problems. Therefore, it is important for teachers to understand students' development and use innovative learning media and involve parents in their children's learning process.